ANALISIS KELAYAKAN BUDIDAYA KERANG HOTATE (MIZUHOPECTEN YESSOENSIS) DI TELUK FUNKA, HOKKAIDO, JEPANG - ELANG KURNIAWAN; TAUFIK BUDHI PRAMONO; AGUNG CAHYO SETYAWAN (Universitas Mahasaraswati K. Mataram, 2023)
Cultivation of Hotate clams (Mizuhopecten yessoensis) in Funka Bay, Hokkaido, Japan, has become an attractive option for farmers. This study assessed the feasibility of Hotate clam (Mizuhopecten yessoensis) culture sites in Funka Bay, Hokkaido, Japan based on water quality data such as temperature, salinity and depth. The analysis showed that the site is highly suitable for Hotate clam culture, with water temperature ranging from 11.5°C to 22.3°C, salinity ranging from 31.01 to 32.97 psu, and culture depth up to 25 meters. Optimal temperatures range from 10°C to 15°C, optimal salinities range from 26 to 32 psu, and suitable depths range from 10 to 30 meters. Appropriate water quality management is an important key in achieving successful Hotate clam culture at this site. The results of the analysis indicate that this site has good suitability for Hotate clam culture. Temperature, salinity and water depth were main factors affecting the cultivation of Hottate mussels and the abundance of invasive organisms